0 < ( x + 144 ) ( x + 67 )
If x > - 67 for example x = - 66
( - 66 + 144 ) ( - 66 + 67 ) = 78 ∙ ( - 1 ) = - 78 which is less than zero.
That is why x must be > - 67
If x > -144 for example x = - 143
( -143 + 144 ) ( - 143 + 67 ) = 1 ∙ ( - 76 ) = - 76 which is less than zero.
That is why x must be < - 144
___________________________________
Remark:
For negative numbers - 66 is greater than - 67
and
- 143 is greater than - 144
____________________________________
So the solution is:
x > - 67 , x < - 144
Solution C
docs.google.com/document/d/1z7NpDHYFABc6rvHOcE_io3zx0JKYhXhDqGyPpzPEzwI/edit?usp=sharing
1 answer